Operational optimization of integrated energy systems considering demand-side flexibility. Issue 1 (1st February 2022) - Wang, Yongli; Zhou, Minhan; Wang, Yanan; Cai, Chengcong; Han, Xu; Chen, Xin; Zhao, Kunpeng
Abstract: In order to solve the operation optimization problem of integrated energy system considering the demand side, this paper takes the integrated energy system of industrial park as the research object and proposes an optimal scheduling model considering the comprehensive demand response. Algorithm analysis shows that RIES containing multiple energy storage devices fully consider the comprehensive demand side response.